Assessment and Distribution of Metal Pollutants in Fadama Soils along River Ngadda and Alau Dam in Maiduguri, Borno State, Nigeria - , P. H. Bukar; , M. O. A. Oladipo; , I. G. E. Ibeanu; , I. Y. Zakari (Archives of Current Research International, 2017)
Elemental metal pollutants concentration levels and their distribution in soils obtained from farmlands along the bank of river Ngadda and Alau dam in Maiduguri, Borno State, North-East of Nigeria is presented. The study was aimed at determining the levels of contamination of soils with metal pollutants used for fadama farming along the bank of river Ngadda and Alau dam with the objectives of assessing the contamination levels of the soils with metal pollutants from the various farmlands at the various sampled sites of study, and the distribution of the various metal pollutant in the various sampled sites. Soil samples were collected from thirteen different sites on the farmlands along the bank of the river and the dam. The samples were analyzed using Instrumental Neutron Activation Analysis (INAA) and the result obtained indicate that the concentration level of some of the elements determined were above maximum allowable concentration (MAC) value while some below the (MAC) values for example the concentration range for Cr was (16 ± 2 – 47 ±3) ppm, Sb was (0.18 ± 0.04 – 14.2 ± 7) ppm, Zn was (21.8 ± 4 – 145 ± 7) ppm and the maximum values for these ranges exceed the (MAC) value recommended for Agricultural soils while the concentration ranges for As was (0.46 ± 0.12 – 1.0 ± 0.2)ppm, Co was (1.6 ± 0.3 – 5.3 ± 0.4) ppm, Vn was (14.6 ± 2.32 – 29 ± 2) ppm with the maximum value for these ranges being below the MAC values given by some countries. The elements obtained from samples collected from different study areas along the bank of river Ngadda and Alau dam were analyzed for similarity distribution of the study area using mathematical tool of cluster analysis technique employing hierarchical procedure and using WARD’s method. The result obtained produce a dendrogram consisting of two clusters comprising of six and seven sites with percentage similarity of 96.5% and 90.8% respectively with one site as an outlier. It is recommended that since some of the trace metals namely Cr, Sb, and Zn assessed in the fadama soils indicates concentrations above the MAC values, they can posed negative health implications to consumers of food which were cultivated on soils from the study area, therefore there is the need to condition the soils before using it for farming so as to make it suitable for food crop farming.